2000
DOI: 10.1039/b001799j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydrogen peroxide in workplace air: interferences and method validation

Abstract: A dynamic system for the generation of stable hydrogen peroxide test atmospheres was applied to the evaluation of samplers used for the determination of hydrogen peroxide in workplace air. The system is able to generate gas mixtures of between 0.1 and 10 ppm at different combinations of relative humidity (20-80%) and temperature (10-30 degrees C). Gaseous hydrogen peroxide is sampled on glass filters impregnated with Ti(IV) chloride and sulfuric acid and analyzed by UV spectroscopy. An interference was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The variance in the quantified H 2 O 2 concentrations is further accentuated when calculating the %FE for H 2 O 2 production following the electrochemical measurement (Figure 4c), where the %FE difference between KMnO 4 titration (80.5 %) and TiOSO 4 (90.3 %) spectrophotometry is almost 10 %, a substantial disparity between the two detection methods. It has been previously reported that the TiOSO 4 method may be susceptible to interferences from anions like CO 3 2− present in the electrolyte [42,43] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variance in the quantified H 2 O 2 concentrations is further accentuated when calculating the %FE for H 2 O 2 production following the electrochemical measurement (Figure 4c), where the %FE difference between KMnO 4 titration (80.5 %) and TiOSO 4 (90.3 %) spectrophotometry is almost 10 %, a substantial disparity between the two detection methods. It has been previously reported that the TiOSO 4 method may be susceptible to interferences from anions like CO 3 2− present in the electrolyte [42,43] …”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that the TiOSO 4 method may be susceptible to interferences from anions like CO 3 2À present in the electrolyte. [42,43]…”
Section: Chemsuschemmentioning
confidence: 99%
“…It is necessary to evaluate the resistivity to hydrogen peroxide and the amount of residual hydrogen peroxide left in the material. There are several analytical methods for the determination of hydrogen peroxide such as reduction by SnCl2 (Egerton et al, 1954), thiocyanate method (Egerton et al, 1954;Ikarashi et al, 1995), enzymatic method of dimerization of p-hydroxyphenolic acid (Christensen, 2000), color changes of Ti 2 (SO 4 ) 3 or TiCl 4 by spectrophotometric detection (Egerton et al, 1954), UV spectroscopy, titration of KMnO 4 , I 3 -, or Ce(SO 4 ) 2 (Klassen et al, 1994), electrochemical, polarographic and other methods (Higashi et al, 2005).…”
mentioning
confidence: 99%
“…For example, H 2 O 2 is quantified in the Li–O 2 battery field by combining titration and spectrophotometry using titanium oxysulfate (TiOSO 4 ) as an assay. , The standard error of the method was reported to be 5.8% at concentrations of 1 ppm of H 2 O 2 . However, anions in electrolytes commonly used for electrochemical water oxidation, i.e., CO 3 – and SO 3 2– , were found to interfere with the determination . Ultimately, regardless of the choice of measurement method, we recommend that the H 2 O 2 quantification procedure be explicitly vetted in the electrochemical environment being studied, and protocols and procedures for performing the measurement should be described in detail to ensure repeatability and to enable comparison across laboratories.…”
mentioning
confidence: 99%
“…39 However, anions in electrolytes commonly used for electrochemical water oxidation, i.e., CO 3 − and SO 3 2− , were found to interfere with the determination. 40 Ultimately, regardless of the choice of measurement method, we recommend that the H 2 O 2 quantification procedure be explicitly vetted in the electrochemical environment being studied, and protocols and procedures for performing the measurement should be described in detail to ensure repeatability and to enable comparison across laboratories.…”
mentioning
confidence: 99%